Multi-stimuli-responsive photonics films based on chiral nematic cellulose nanocrystals. (1st February 2022) - Meng, Yahui; He, Zhibin; Dong, Cuihua; Long, Zhu
Abstract: Multiple-stimuli-responsive bio-based materials have received considerable attention for intelligent packaging and anti-counterfeiting applications. Herein, we present a unique biobased photonics film with multi-stimuli responsive behavior based on cellulose nanocrystals (CNCs), sorbitol (S) and anthocyanin (Anth). The resulting photonics film exhibits multi-stimuli responsive behavior to humidity, solvent and pH stimuli. Notably, the photonics film showed dramatic invertible color from blue to fuchsia and high sensitivity at a relative humidity from 50% to 100%. Moreover, the photonics film exhibited fast response and good reversibility under different ethanol concentrations. Significant color changes of the photonics film were also observed in response to pH change in the range of 2 to 12. Particularly, the humidity, solvent and pH responsiveness of the photonics film did not interfere with each other.